Cultural Literacy in Literary Learning: Enhancing Students’ Figurative Language Analysis through Discovery Learning - Wulansari, Yolandia Dwi; Saputra, Ardi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study examines the effectiveness of the Discovery Learning model in enhancing students' ability to analyze figurative language in short stories. Conducted with 29 ninth-grade students at SMP Santa Maria Sidoarjo during the 2025/2026 academic year, the Classroom Action Research (CAR) design included two cycles of planning, action, observation, and reflection. Data were gathered through written tests, classroom observations, and documentation to assess students' analytical skills and engagement. Results showed significant improvement in analyzing figurative language, with average scores rising from 48.62 in the pre-cycle to 62.28 in Cycle I and 78.40 in Cycle II, surpassing the minimum mastery criterion. Additionally, the learning process fostered greater student participation and critical thinking during literary analysis. These findings indicate that Discovery Learning is an effective approach for developing literary competence and interpretative skills, while also enhancing cultural literacy in alignment with Education for Sustainable Development goals by promoting critical awareness and engagement with literary texts.